Tax projections in German states – manipulated by opportunistic incumbent parties? - Ivo Bischoff; Wolfgang Gohout (Justus-Liebig-Universität Gießen, Fachbereich Wirtschaftswissenschaften, 2006)
This paper analyses the accuracy of the tax projections of West German states from a public choice perspective. It argues that state governments have the possibility and face incentives to manipulate tax projections. Evidence for the years 1992 - 2002 reveals a general upward bias in tax projections in election as well as non-election years. The degree of overestimation is higher, the less popular the incumbent party is. Partisanship and elections have no significant influence. To improve external control of state governments in the budget process, the process of tax projections must be made transparent.
Keywords: D72; H72; 330; tax projections; political parties; budget process; public expenditures